Consciousness and the Environment: Maharishi Technologies of Consciousness and the Incidence of U.S. Landfalling Hurricanes, 1851–2021 - Cavanaugh, Kenneth L.; Fergusson, Lee (Journal of Scientific Exploration, 2025)
The purpose of this preliminary study is to explore whether application of consciousness-based procedures whose stated purpose is to influence the natural and social environment, referred to as Maharishi Technologies of Consciousness (MTC), can positively affect weather phenomena. The theoretical framework underlying these procedures is based on a field-theoretic view of consciousness derived from the ancient Vedic tradition of knowledge of consciousness from India as revived by Maharishi Mahesh Yogi. Seven peer-reviewed articles published in independent scholarly journals since 2016 have reported statistically and practically significant associations between the application of the two key modalities of MTC and the reduction of stress and tension in the field of collective consciousness of society, as measured by significantly reduced rates of U.S. homicide and urban violent crime, fatality rates from motor vehicle and other accidents, drug-related death, and infant mortality. The current study presents results of an interrupted time series analysis (ITS) of data from a quasi experiment. The quasi-experiment was designed to empirically test, after controlling for other explanatory variables, whether application of MTC during a demonstration period 2006–2014 was associated with a reduction in the mean annual predicted count of landfalling hurricanes (LFH) striking the continental U.S. relative to the historical baseline mean 1851–2005. A second hypothesis was that the mean LFH count would increase after discontinuation of MTC during 2015–2021. Data for LFH and control variables were obtained from the U.S. National Oceanic and Atmospheric Administration (NOAA). A second (replication) study applied the same regression methods for count data (quasi-Poisson regression) to analyze a subsample of NOAA data for 1900 2021. For both analyses the empirical results were consistent with hypotheses (1) and (2). The observed decline of landfalling hurricanes during the 2006–2014 demonstration period was largely coincident with an unexpected, historically unprecedented 2006–2016 period of reduced LFH that has been termed the hurricane drought by hurricane experts. We conclude with a discussion of potential alternative explanations and suggested directions for future research.